An Extremely Rare Presentation of an Alpha-Fetoprotein-Producing Esophageal Adenocarcinoma - Khalid, Yaser (Case Rep Gastroenterol, 2020)
Alpha-fetoprotein (AFP)-producing esophageal adenocarcinoma (EAC) is an extremely rare occurrence with very few cases reported in the literature. We report the case of a 76-year-old female who presented with progressive weakness, fatigue, and a decrease in appetite for weeks and who was found to have an AFP-producing EAC with an extraordinarily high AFP level of 46,135 ng/mL. CT angiography revealed abnormal thickening of the esophagus and multiple metastatic masses throughout the liver. Upper endoscopy revealed a large mass in the distal esophagus with extension into the stomach. Biopsy confirmed the EAC. Most cases are unsuccessfully treated with surgery and chemotherapy. Serial measurement of serum AFP may be useful for monitoring clinical status and treatment response.